Ambidexterity behavior of creative SMEs for disruptive flows of innovation: A comparative study of Indonesia and Taiwan - Nahiyah Jaidi; Siswantoyo; Jane Liu; Zahrotush Sholikhah; Mega Murti Andhini (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Disruptive innovation forces small-business managers to innovate by carrying out exploitation and exploration activities simultaneously. This ambidexterity is crucial to the survival of today's businesses, especially small and medium-sized enterprises (SMEs). In the organizational structure of SMEs, the manager and owner play an essential role in determining the business orientation. This study examined the influence of SME managers' social networks on the organization's ambidexterity and its impact on the firm's innovation performance. This study used two moderating variables in the form of two internal factors in respect to managers: how proactive they are and their commitment to innovation. The study population was drawn from SMEs in the creative manufacturing sector in Indonesia and Taiwan, with a total sample of 224 SMEs, including 101 from Indonesia and 123 from Taiwan. The analytical technique was the PLS-SEM, conducted by the Smart-PLS software version 3.3.6: Hamburg, Germany. The results supported the construction in both countries. The results of the multiple-group analysis show that the SMEs in Indonesia exhibited greater ambidexterity, commitment to innovation, and innovation performance than those in Taiwan.
Keywords: 650; SMEs; ambidexterity; commitment to innovation; innovation performance; managerial social networks; proactive managerial